RADI-20. RETROSPECTIVE OUTCOME ANALYSIS OF INTRAOPERATIVE RADIOTHERAPY (IORT) FOR SURGICALLY RESECTED BRAIN METASTASES: AN INTERNATIONAL COOPERATIVE STUDY. (12th August 2019) - Cifarelli, Christopher; Vargo, J Austin; Hack, Joshua; Kahl, K Henning; Brehmer, Stefanie; Sarria, Gustavo; Giordano, Frank
Abstract: BACKGROUND & OBJECTIVE: The ideal delivery of adjuvant radiation to the surgical cavity of brain metastases (BMs) remains the subject of debate. Risks of leptomeningeal dissemination (LMD), local failure (LF) and radiation necrosis (RN) have prompted a reappraisal of the timing and/or modality of this critical component of BM management. IORT delivered at the time of resection for BMs requiring surgery offers the potential for improved LC and decreased LMD afforded by the elimination of delay in time to initiation of radiation following surgery and the possibility of dose escalation beyond that seen in stereotactic radiosurgery (SRS). This study provides a retrospective analysis with identification of potential predictors of outcomes. METHODS: Retrospective data was collected on patients treated with IORT immediately following surgical resection of BMs at three institutions according to the approval of individual IRBs. All patients were treated with the Zeiss Intrabeam device (Carl Zeiss Meditech, Germany) using spherical applicators ranging from 1.5 to 4.0cm with 50kV output. Statistical analyses were performed using SPSS (IBM) with endpoints of LF, DBF, incidence of RN, and overall survival (OS) and p< 0.05 considered significant. RESULTS: 54 patients were treated with IORT with a median age of 64 years. The most common primary diagnosis was non-small cell lung cancer (40%) with the most common location in the frontal lobe (38%). Median follow-up was 7.2 months and 1-year LC, DBF, and OS were 88%, 58%, and 73%, respectively. LMD was identified in 2 patients (3%) and RN present in 4 patients (7%). The only predictor of LC was extent of resection with 1-yr LC of 94% for GTR vs 62% for STR (p=0.049). CONCLUSIONS: IORT is a safe and effective means of delivering adjuvant radiation to the BM resection cavities with high rates of LC and low incidence of RN.